FAKTOR YANG MEMPENGARUHI PASIEN TUBERKULOSIS RESISTAN OBAT YANG TIDAK MEMULAI PENGOBATAN: LITERATURE REVIEW - Indri Rizkiyani; Syahrizal Syarif (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Drug-resistant tuberculosis (DR TB) patients who have been diagnosed but not enrolled to treatment could be a source of primary transmission and the risk of increasing DR TB cases in the community. The aim of this literature review is to determine the factors that influence pre-treatment lost to follow up of DR TB patients by searching the literature through Google Scholar, ScienceDirect, ProQuest and PubMed which was published in the period 2016 to 2023 with the keywords